Auditoria na merenda escolar impacta a taxa de rendimento dos alunos?: estimação do efeito de um programa de fiscalização sobre os estudantes de escolas municipais - SILVA, Leidian Moura da (2021)
It was sought to identify the effect of audits in the School Feeding Program on the performance rates of students in municipal schools. For this, for this, the pass, failure and abandonment rates of students were used in the 5th year of elementary school, between 2011 and 2018, from the municipalities eligible for the Third Cycle of Inspection of the Comptroller General of the Union (CGU), which occurred in 2016. For the analysis, randomization methods were used, employed by the CGU in the selection of inspected municipalities, and diff-in-diff were used for robustness of the results. The results did not identify an effect on the failure and dropout rates, however, the approval rate was positive in the estimation of the general averages and two years after the audit. Thus, it is possible to assume structural changes in the management of school meals, enabling the PNAE resources to be used to achieve its objectives of, through the feeding, contribute to the development and learning of public school students.